Perceptions about the experiences of the novice english professors during their first years working in the Foreign Language Department, School of Arts and Sciences, University of El Salvador - Torres Cartagena, Jorge Eduardo
The following paper has the main objective to demonstrate the experiences that Novice English professors face, the difficulties they have to overcome as well as the relationships with their colleagues during their first years teaching at the Foreign Language Department in the University of El Salvador. To begin with, it is presented some definitions of what a novice professor is, also some historical background regarding how the teaching process has evolved over the years. In addition, it is stated the reasons behind why they decide to become a professor at a University level. Furthermore, the research team highlights the main aspects involved in the teaching process such as points of view, thoughts, impressions, opinions, motivation and attitudes. Afterwards, the outcomes demonstrate that there is a lack of trainings regarding the inductions before starting the teaching process. It is pointed out that novice professors need guidance from experienced colleagues aside from the need of technological gadgets from the Foreign Language Department. On top of that, some other delicate concerns are presented that have not been addressed yet by the authorities of the Foreign Language Department. Finally, some suggestions are offered to the Foreign Language Department in order to provide continuous improvement to the performance of the novice English professors.